Design and Synthesis of Heterocyclic Encapsulated Organosilatranes for In Silico, In Vitro Antioxidant and Cytotoxicity Evaluation. Issue 47 (17th December 2020) - Singh, Gurjaspreet; Sharma, Geetika; Satija, Pinky; Singh, Akshpreet; Pawan; Ruiz, Cristóbal E.; Silvera, Daniel G.; Esteban, María A.; Soni, Sajeev
Abstract: Provoked by multifarious applicability of nitrogen heterocycles and hypervalent silicon analogues in drug designing, we attempted the synthesis and structural characterization of a family of heterocyclic appended Organosilatranes tethered with an azomethine linkage by employing a three‐step preparation route and carried out introspection into their prospective bioactivities. Using MOLINSPIRATION and ADMET toolkits, pharmacokinetic profiles of the designed scaffolds were investigated and the results showed their potential as promising drug candidates. The article also assesses the antioxidant potential and cytotoxicity property of the synthesized organosilatranes, which are required is to prevent the oxidative stress in the body formed of reactive species. It was observed that compounds 10 –12 with methyl substituents on the atrane rings can be the best pretenders for radical scavenging activity while the cytotoxicity evaluation revealed that the compounds 7, 8 and 10 are least toxic of all examined organosilatranes. Abstract : N ‐Heterocyclic organosilatranes bridged through azomethine linkage have been constructed using a three‐step synthetic methodology and characterized using different analytical and spectroscopic techniques such as IR, NMR and elemental analysis. The synthesized compounds were first screened in silico and further assessed for antioxidant analysis and cytotoxicity evaluation. Moreover, the biological potential of the obtained organosilatranes have been screened by employing Molinspiration and ADMET software.